2005
DOI: 10.1186/1471-2334-5-111
|View full text |Cite
|
Sign up to set email alerts
|

The role and performance of chest X-ray for the diagnosis of tuberculosis: A cost-effectiveness analysis in Nairobi, Kenya

Abstract: Background: The objective of this study was to establish 1) the performance of chest X-ray (CXR) in all suspects of tuberculosis (TB), as well as smear-negative TB suspects and 2) to compare the cost-effectiveness of the routine diagnostic pathway using Ziehl-Neelsen (ZN) sputum microscopy followed by CXR if case of negative sputum result (ZN followed by CXR) with an alternative pathway using CXR as a screening tool (CXR followed by ZN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 5 publications
(5 reference statements)
7
83
0
Order By: Relevance
“…1,10 Use of these guidelines is supported by a Kenyan study which showed that TB diagnosis by direct smear microscopy followed by CXR is more cost-effective compared to diagnosis by CXR alone. 17 This was a district-based study, where data were collected for TB patients under routine programmatic conditions. The study included large numbers of patients, and we believe that the results are representative of the national situation.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Use of these guidelines is supported by a Kenyan study which showed that TB diagnosis by direct smear microscopy followed by CXR is more cost-effective compared to diagnosis by CXR alone. 17 This was a district-based study, where data were collected for TB patients under routine programmatic conditions. The study included large numbers of patients, and we believe that the results are representative of the national situation.…”
Section: Discussionmentioning
confidence: 99%
“…26 The incidence of PTB in our patient cohort was much lower than expected, and although screening with chest X-rays (CXR) and sputum are performed routinely on every patient at the time of program enrollment, the low sensitivity and specificity of this type of screening is well known. 27,28 Potentially, more patients had undiagnosed PTB at ART initiation and were at higher risk of adverse outcomes than those who were actually diagnosed, perhaps because they were monitored less closely for other comorbidities such as the immune reconstitution inflammatory syndrome (IRIS) or were less likely to be receiving prophylactic co-trimoxazole.…”
Section: Discussionmentioning
confidence: 99%
“…In establishing the performance of chest X-ray (CXR) in all suspects of tuberculosis (TB), a study by van Cleeff et al [14] showed 89% agreement (K = 0.75) for the combined scores "TB" or "no-TB". For the detection of ADP, inter-observer agreement was good (K = 0.61) between pneumologists and moderate (K = 0.55) between radiologists.…”
Section: Discussionmentioning
confidence: 99%